If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 18y + 1 Reorder the terms: y = 1 + 18y Solving y = 1 + 18y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18y' to each side of the equation. y + -18y = 1 + 18y + -18y Combine like terms: y + -18y = -17y -17y = 1 + 18y + -18y Combine like terms: 18y + -18y = 0 -17y = 1 + 0 -17y = 1 Divide each side by '-17'. y = -0.05882352941 Simplifying y = -0.05882352941
| 9-2(3x-5)=2(3-4x) | | 18y+1=y | | 6+3*5+6= | | 2(x-2)=5x+5-3(-3x-2) | | 6=j | | 9(0)-3y=-81 | | 6+3*6+6= | | 3+3*6+6= | | 0.2y=1600-8400 | | x^2-24x+27=0 | | 0.2y=8400-1600 | | 3x-24=1x+10 | | 9x-3(0)=-81 | | 8w^2+2w-1=0 | | 2+2p=6 | | 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 |